Positive electrode active material for lithium ion secondary battery and method for producing same, lithium ion secondary battery
The introduction of a lithium-nickel-manganese composite oxide positive electrode active material, incorporating titanium and optimized through specific manufacturing steps, addresses the challenge of achieving high thermal stability and battery capacity in lithium-ion secondary batteries, particularly with high nickel ratios.
Patent Information
- Application Number
- JP2020161397
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-09-25
AI Technical Summary
Existing lithium-ion secondary batteries face challenges in achieving high thermal stability while maintaining high battery capacity and output characteristics, especially with high nickel ratio positive electrode active materials.
A positive electrode active material composed of lithium-nickel-manganese composite oxide with a hexagonal layered structure, incorporating titanium and other elements, is developed. This material is produced through a method involving calcination at specific temperatures in an oxidizing atmosphere, followed by water washing and drying steps to enhance thermal stability and battery performance.
The proposed positive electrode active material achieves high thermal stability and battery capacity, even at high nickel ratios, while allowing for easy industrial-scale production, thus addressing the limitations of existing technologies.
Smart Images

Figure 0007665942000004 
Figure 0007665942000005 
Figure 0007665942000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery, a method for producing the same, and a lithium ion secondary battery. [Background technology]
[0002] In recent years, with the widespread use of portable electronic devices such as mobile phone terminals and notebook computers, there has been a strong demand for the development of small, lightweight non-aqueous electrolyte secondary batteries that have high energy density and durability. There has also been a strong demand for the development of high-output secondary batteries for use in power tools and electric vehicles, including hybrid vehicles.
[0003] Non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries are available as secondary batteries that meet these requirements. Lithium ion secondary batteries that use layered or spinel-type lithium metal composite oxides as the positive electrode material can obtain a high voltage of about 4 V, and are therefore being put to practical use as batteries with high energy density.
[0004] Lithium metal composite oxides include lithium cobalt composite oxide (LiCoO2), which is relatively easy to synthesize, lithium nickel composite oxide (LiNiO2), which uses nickel, which is cheaper than cobalt, and lithium nickel cobalt manganese composite oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), lithium manganese composite oxide (LiMn2O4), lithium nickel manganese composite oxide (LiNi 0.5 Mn 0.5 O2) have been proposed.
[0005] However, when a non-aqueous electrolyte is used as a battery material, lithium ion secondary batteries are required to have high thermal stability. For example, when a short circuit occurs inside a lithium ion secondary battery, heat is generated due to a sudden current, so that higher thermal stability is required.
[0006] Therefore, we developed a lithium nickel cobalt manganese composite oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) and lithium nickel manganese composite oxides are attracting attention. Lithium nickel cobalt manganese composite oxides, like lithium cobalt composite oxides and lithium nickel composite oxides, are layered compounds, and those with a 1:1:1 composition ratio of nickel, cobalt, and manganese in the transition metal sites are called ternary positive electrode active materials.
[0007] Furthermore, in recent years, ternary positive electrode active materials and positive electrode active materials with a high nickel ratio (Hi-Ni positive electrode material) that increase the nickel ratio in lithium nickel manganese composite oxides have been attracting attention in order to increase capacity. However, the increase in battery capacity due to the nickel ratio comes with a trade-off with a decrease in thermal stability, so there is a demand for positive electrode active materials that combine high performance (high capacity, high cycle characteristics, high output, etc.) with short-circuit resistance and thermal stability as lithium-ion secondary batteries.
[0008] In order to improve battery characteristics such as thermal stability, several techniques have been proposed for adding different elements such as niobium to lithium metal composite oxides. For example, Patent Document 1 proposes a positive electrode active material for non-aqueous secondary batteries that is made of a composition composed of at least one compound composed of lithium, nickel, cobalt, element M, niobium, and oxygen. In this proposal, it is said that a positive electrode active material with high thermal stability and large discharge capacity can be obtained because the Li-Nb-O-based compound present near the surface or inside the particles has high thermal stability.
[0009] Patent Document 2 describes a positive electrode active material for a non-aqueous electrolyte secondary battery, which is made of a lithium transition metal composite oxide obtained by a manufacturing method including a niobium coating step and a firing step, and has a porous structure and a specific surface area of 2.0 to 7.0 m. 2 / g. It is said that the use of this positive electrode active material can provide a non-aqueous electrolyte secondary battery that has high safety, battery capacity, and excellent cycle characteristics.
[0010] Patent Document 3 also proposes a positive electrode active material for non-aqueous electrolyte secondary batteries having at least a layered lithium transition metal composite oxide, the lithium transition metal composite oxide being present in the form of particles consisting of either or both of primary particles and secondary particles which are aggregates thereof, and having a compound having at least one selected from the group consisting of molybdenum, vanadium, tungsten, boron and fluorine on at least the surface of the particles. It is said that the conductivity is improved by having the compound on the surface of the particles.
[0011] Patent Document 4 proposes a lithium transition metal compound powder for use as a positive electrode material for lithium secondary batteries, which is made by adding a compound containing at least one element selected from B and Bi and a compound containing at least one element selected from Mo, W, Ti, Ta, and Re to the main component raw material in combination and then firing the compound, and by adding the additive elements in combination and then firing the compound. It is said that by adding the additive elements in combination and then firing the compound, it is possible to obtain a lithium-containing transition metal compound powder that is easy to handle and easy to prepare electrodes.
[0012] Patent Document 5 proposes a positive electrode composition for non-aqueous electrolyte secondary batteries that contains a lithium transition metal composite oxide and a boron compound that contains at least boron and oxygen elements. It is said that the use of a positive electrode composition that contains a lithium transition metal composite oxide that contains nickel and tungsten as essential elements and a specific boron compound can improve the output characteristics and cycle characteristics of the positive electrode composition that uses the lithium transition metal composite oxide.
[0013] Patent Document 6 proposes a positive electrode active material for non-aqueous electrolyte secondary batteries, which is made of a lithium nickel manganese composite oxide composed of a hexagonal lithium-containing composite oxide having a layered structure, has an average particle size of 2 to 8 μm, an index showing the spread of the particle size distribution [(d90-d10) / average particle size] of 0.60 or less, and has a hollow structure consisting of an outer shell part formed by sintering aggregated primary particles and a hollow part present inside the shell part. This positive electrode active material is said to have high capacity and good cycle characteristics when used in non-aqueous secondary batteries, enabling high output.
[0014] Furthermore, Patent Document 7 describes that by adding 1 to 10% by molar ratio of zirconium to cobalt to a lithium-cobalt composite oxide, the surfaces of the lithium-cobalt composite oxide particles are covered with zirconium oxide or a composite oxide of lithium and zirconium, and when the lithium-cobalt composite oxide is used in the positive electrode of a secondary battery, the decomposition reaction of the electrolyte at high potential and crystal destruction are suppressed, and excellent cycle characteristics and storage characteristics are exhibited. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] JP 2002-151071 A [Patent Document 2] International Publication No. 2014 / 034430 [Patent Document 3] JP 2005-251716 A [Patent Document 4] JP 2011-108554 A [Patent Document 5] JP 2013-239434 A [Patent Document 6] International Publication No. 2012 / 131881 [Patent Document 7] Japanese Patent Application Publication No. 4-319260 Summary of the Invention [Problem to be solved by the invention]
[0016] However, although the above proposals all show improvements in battery capacity, output characteristics, and durability, they do not sufficiently improve thermal stability, and further improvement in thermal stability is desired.
[0017] As a method to improve thermal stability during overcharging, a method of coating the surface of the positive electrode active material with oxides such as SiO2, Al2O3, and ZrO2 has been proposed. However, this method results in a large initial capacity loss and a decrease in output characteristics due to the coating layer acting as resistance. In addition, the process is complicated and difficult to scale up, making industrial-scale production difficult in many cases.
[0018] In addition, as proposed above, a method of adding a different element to a positive electrode active material to improve thermal stability during overcharging has also been proposed. However, in a positive electrode active material with a high nickel ratio, cation mixing, in which metal elements such as nickel migrate to the lithium ion site, is likely to occur, so the firing temperature must be lower than that of a positive electrode active material with a low nickel ratio, and the different element is less likely to form a solid solution in the active material.
[0019] The present invention has been made in consideration of these circumstances, and aims to provide a positive electrode active material that can provide a lithium ion secondary battery that achieves both excellent battery capacity and high thermal stability at a high level. Another aim of the present invention is to provide a method for easily producing such a positive electrode active material in industrial-scale production. [Means for solving the problem]
[0020] In a first aspect of the present invention, there is provided a positive electrode active material for a lithium ion secondary battery, comprising a lithium nickel manganese composite oxide composed of secondary particles formed by agglomeration of a plurality of primary particles, The lithium nickel manganese composite oxide has a hexagonal layered structure and contains lithium (Li), nickel (Ni), manganese (Mn), an element M (M) which is at least one element selected from Co, V, Mg, Mo, Ca, Cr, Ta, Na, W, Fe, Zn, B, Si, P, Zr, Nb, and Al, and titanium (Ti), and the ratio of the amounts of substances of the respective elements is Li:Ni:Mn:M:Ti=a:(1-xyz):x:y:z (where 0.97≦a ≦1.25, 0.03≦x≦0.15, 0≦y≦0.15, 0.01≦z≦0.05), and in an XRD measurement of the positive electrode active material, the ratio of the total amount of peak intensities of the strongest lines of the titanium compound to the (003) diffraction peak intensity, which is the strongest line of the hexagonal layered structure, is 0.2 or less, the (003) crystallite diameter measured by XRD is 80 nm or more and less than 160 nm, and the specific surface area measured by the BET method is 0.7 m 2 / g or more 4.0m 2 / g or less, A positive electrode active material for a lithium ion secondary battery is provided.
[0021] In addition, the particle size distribution distribution index [(D90-D10) / Mv] calculated from the volume-based D90 and D10 in the particle size distribution by the laser diffraction scattering method and the volume average particle size (Mv) is preferably 0.80 to 1.20. In addition, the volume average particle size Mv is preferably 8 μm to 20 μm. In addition, the amount of lithium dissolved in water when immersed in water is preferably 0.2 mass% or less with respect to the entire positive electrode active material.
[0022] In a second aspect of the present invention, there is provided a method for producing a positive electrode active material for a lithium ion secondary battery, comprising a lithium nickel manganese composite oxide composed of secondary particles formed by agglomeration of a plurality of primary particles, the method comprising at least a mixing step of adding a mixture containing a nickel manganese composite compound, a titanium compound, and a lithium compound, a firing step of firing the mixture at 700° C. or more and 950° C. or less in an oxidizing atmosphere having an oxygen concentration of 80% by volume or more and 100% by volume or less to obtain a lithium nickel manganese composite oxide, a water washing step of mixing 100 parts by mass of the lithium nickel manganese composite oxide with 50 parts by mass or more and 200 parts by mass or less of water, stirring the mixture, and then separating the mixture into a solid-liquid state, and a drying step of drying the lithium nickel manganese composite oxide after washing with water, the nickel manganese composite compound being composed of nickel (Ni), manganese (Mn), Co, V, Mg, Mo, Ca, Cr, Ta, Na, W, Fe, Zn, and element M (M), which is at least one element selected from B, Si, P, Zr, Nb, and Al, and the ratio of the amounts of substance of each element is Ni:Mn:M=(1-xy):x:y (where 0≦x≦0.15, 0≦y≦0.15), and the mixture obtained in the mixing step has a ratio (Li / Me) of the amount of substance of lithium (Li) to the total amount of substance (Me) of nickel, manganese, element M, and titanium contained therein, which is 0.97 or more and 1.2 or less. the ratio (Ti / Me) of the amount of titanium (Ti) is 0.01 or more and 0.05 or less, in an XRD measurement of the positive electrode active material, the ratio of the total amount of peak intensities of the strongest lines of the titanium compounds to the (003) diffraction peak intensity, which is the strongest line of the hexagonal layered structure, is 0.2 or less, and the (003) crystallite diameter by XRD measurement is 80 nm or more and less than 160 nm is provided.
[0023] The titanium compound preferably has a volume average particle size Mv of 0.01 μm or more and 5 μm or less, and is preferably a titanic acid compound or titanium oxide.
[0024] In a third aspect of the present invention, there is provided a lithium ion secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, in which the positive electrode contains the above-mentioned positive electrode active material. Effect of the Invention
[0025] According to the present invention, it is possible to provide a positive electrode active material capable of obtaining a lithium ion secondary battery that achieves both high battery capacity and high thermal stability at a high level. Moreover, the present invention makes it possible to easily produce such a positive electrode active material in industrial-scale production, and thus the industrial value of the present invention is extremely great. [Brief description of the drawings]
[0026] [Figure 1] The upper part of FIG. 1 is a graph showing the maximum oxygen evolution peak intensity of the positive electrode active materials obtained in Comparative Examples 1 to 3, and 4, and Example 1, and the lower part of FIG. 1 is a graph showing the initial discharge capacity of the positive electrode active materials obtained in Comparative Examples 1 to 3, and 4, and Example 1, and a table showing the titanium content, peak intensity ratio, and whether or not each material was washed with water. [Diagram 2] FIG. 2 is a graph showing the initial discharge capacity of the positive electrode active materials obtained in Comparative Example 1 and Comparative Example 2. As shown in FIG. [Diagram 3] FIG. 3 is a graph showing the initial discharge capacity of the positive electrode active materials obtained in Comparative Example 3 and Example 1. [Figure 4] FIG. 4 is a diagram showing an example of a method for producing a positive electrode active material for a lithium ion secondary battery according to this embodiment. [Diagram 5] 5(A) and 5(B) are diagrams showing an example of a method for producing the nickel-manganese composite compound according to this embodiment. [Figure 6] FIG. 6 is a schematic cross-sectional view of a coin-type battery used in the battery evaluation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, the present embodiment will be described with respect to a positive electrode active material for a lithium ion secondary battery, a method for producing the same, and a lithium ion secondary battery. Note that the present embodiment described below does not unduly limit the contents of the present invention described in the claims, and can be modified within the scope of the present invention. In addition, not all of the configurations described in the present embodiment are necessarily essential as a means for solving the present invention.
[0028] 1. Positive electrode active material for lithium-ion secondary batteries The positive electrode active material for a lithium ion secondary battery according to this embodiment (hereinafter also referred to as the "positive electrode active material") contains a lithium nickel manganese composite oxide composed of secondary particles formed by aggregation of a plurality of primary particles. That is, the lithium nickel manganese composite oxide is composed of particles with a polycrystalline structure.
[0029] The lithium nickel manganese composite oxide has a hexagonal layered structure and contains lithium (Li), nickel (Ni), manganese (Mn), element M (M) which is at least one element selected from Co, V, Mg, Mo, Ca, Cr, Ta, Na, W, Fe, Zn, B, Si, P, Zr, Nb, and Al, and titanium (Ti) in specific ranges.
[0030] Lithium ion secondary batteries require high thermal stability, especially when they use a flammable non-aqueous electrolyte as a constituent material. For example, when a positive electrode and a negative electrode are short-circuited due to the inclusion of a metallic foreign object or the like in a charged state, a short-circuit current is generated, and the heat generated by the short-circuit current causes the positive electrode active material to decompose, releasing oxygen from the crystals, which reacts with the electrolyte, causing thermal runaway.
[0031] As a method for improving the thermal stability of secondary batteries during charging, as described above, a method of coating the surface of the positive electrode active material with oxides such as SiO2, Al2O3, and ZrO2 has been proposed. However, with this method, the initial capacity loss is large, and the coating layer becomes a resistance, resulting in a decrease in output characteristics. In addition, a method of adding a different element to the positive electrode active material to improve the thermal stability during overcharging has also been proposed, but in a positive electrode active material with a high nickel ratio, cation mixing, in which metal elements such as nickel migrate to the lithium ion site, is likely to occur, so the baking temperature must be lower than that of a positive electrode active material with a low nickel ratio, and the different elements are difficult to dissolve in the positive electrode active material, so when the different elements are added, it is difficult to improve the thermal stability during overcharging while maintaining a high battery capacity.
[0032] As a result of intensive research, the present inventors have discovered that by i) adding a specific amount of titanium to a lithium nickel manganese composite oxide having a high nickel ratio and containing a specific amount of manganese, and then firing the oxide under controlled atmosphere with a high oxygen concentration, it is possible to achieve both high battery characteristics (e.g., battery capacity) and thermal stability by suppressing oxygen release during overcharge, and ii) further, by washing the lithium nickel manganese composite oxide after firing, the battery capacity can be further improved, which has led to the completion of the present invention.
[0033] Hereinafter, an example of the effect of containing titanium (Ti) in the lithium nickel manganese composite oxide according to this embodiment will be described with reference to Figures 1 to 3. Note that Figures 1 to 3 are created based on the evaluation results of the positive electrode active material and secondary battery obtained in the examples and comparative examples described later.
[0034] FIG. 1 is a graph showing the evaluation results of maximum oxygen evolution peak intensity and initial discharge capacity using lithium nickel manganese composite oxides (positive electrode active materials) that differ in titanium content and distribution, and whether or not they were washed with water and dried after firing.
[0035] The maximum oxygen generation peak intensity is the relative intensity (Comparative Example 1 is taken as 100) of the amount of oxygen generated when a lithium nickel manganese composite oxide (positive electrode active material) is overcharged and heated from room temperature to 450°C, and the lower this value, the smaller the amount of oxygen generated and the higher the thermal stability during overcharging.
[0036] As shown in the upper graph of FIG. 1, the titanium-containing positive electrode active materials of Comparative Example 3, Comparative Example 4, and Example 1 have reduced maximum oxygen evolution peak intensity and improved thermal stability, compared to the titanium-free positive electrode active materials of Comparative Examples 1 and 2.
[0037] Furthermore, as shown in the lower graph of FIG. 1, the positive electrode active material of Example 1, which contains titanium, has a peak intensity ratio of 0.2 or less, and has been washed with water and dried, has a significantly improved initial discharge capacity compared to the positive electrode active material of Comparative Example 3, which contains titanium but has not been washed with water or dried, and the positive electrode active material of Comparative Example 4, which has a peak intensity ratio of more than 0.2.
[0038] As described below, the peak intensity ratio refers to the ratio of the total peak intensity of the strongest line of the diffraction peak derived from each titanium compound (titanium oxide, lithium titanate, etc.) to the (003) diffraction peak intensity, which is the strongest line of the hexagonal layered structure. For example, as in Comparative Example 3 and Example 1 in FIG. 1, when the peak intensity ratio is 0.2 or less, it indicates that titanium is almost dissolved in the primary particles of the lithium nickel manganese composite oxide. Also, as in Comparative Example 4 in FIG. 1, when the peak intensity ratio exceeds 0.2, it indicates that a titanium compound is formed on the particle surface of the lithium nickel manganese composite oxide.
[0039] From the above results, it is clear that the positive electrode active material containing the lithium nickel manganese composite oxide according to this embodiment i) has high thermal stability despite its high nickel ratio, and ii) by washing with water and drying after firing, the battery capacity is further improved, and it is possible to achieve both high battery capacity and high thermal stability at a higher level.
[0040] FIG. 2 is a graph showing the results of evaluation of the initial discharge capacity of the positive electrode active materials of Comparative Example 1 and Comparative Example 2 which did not contain titanium and were obtained under similar production conditions except for the presence or absence of washing with water and drying. FIG. 3 is a graph showing the results of evaluation of the initial discharge capacity of the positive electrode active materials of Comparative Example 3 and Example 1 which contained titanium and were obtained under similar production conditions except for the presence or absence of washing with water and drying.
[0041] As shown in Figure 2, in lithium nickel manganese composite oxides that have a high nickel ratio and a specific amount of manganese, and do not contain titanium, washing with water and drying after firing reduces the battery capacity (initial discharge capacity). Although the details of the reason for this are unclear, it is thought that washing with water dissolves lithium from the particle surfaces and grain boundaries of the lithium nickel manganese composite oxide, increasing the reaction resistance and thus reducing the battery capacity.
[0042] On the other hand, as shown in Fig. 3, when titanium is contained, the battery capacity (initial discharge capacity) is significantly improved in the positive electrode active material of Example 1 which was washed with water, compared to Comparative Example 3 which was not washed with water and dried. Although the details of the reason for this are unclear, it is presumed that the titanium dissolved inside the primary particles has the effect of suppressing deterioration of the particle surface and grain boundaries due to the elution of lithium and suppressing an increase in reaction resistance.
[0043] As described later, titanium can be dissolved in the primary particles by containing a specific amount of manganese, controlling the firing atmosphere in the firing step (S20) to a high oxygen concentration, or by appropriately adjusting the manufacturing conditions. Therefore, the positive electrode active material according to this embodiment contains specific amounts of titanium and manganese in a positive electrode active material with a high nickel ratio, titanium is almost dissolved in the primary particles, and further, by washing with water and drying, high battery capacity and high thermal stability can be achieved at a higher level. The configuration of the positive electrode active material according to this embodiment will be described in detail below.
[0044] [Lithium nickel manganese composite oxide] The lithium nickel manganese composite oxide contained in the positive electrode active material according to this embodiment is composed of secondary particles formed by agglomeration of a plurality of primary particles.
[0045] The lithium nickel manganese composite oxide has a hexagonal layered structure and contains lithium (Li), nickel (Ni), manganese (Mn), element M (M) which is at least one element selected from Co, V, Mg, Mo, Ca, Cr, Ta, Na, W, Fe, Zn, B, Si, P, Zr, Nb, and Al, and titanium (Ti). The ratio of the amounts of substances of the elements is expressed as Li:Ni:Mn:M:Ti=a:(1-xyz):x:y:z (where 0.97≦a≦1.25, 0.03≦x≦0.15, 0≦y≦0.15, and 0.01≦z≦0.05).
[0046] In addition, in the positive electrode active material according to the present embodiment, almost no diffraction peaks other than those of the hexagonal layer structure are detected in the X-ray diffraction (XRD) measurement, so it can be said that the titanium is almost entirely dissolved in the primary particles. In addition, the (003) crystallite diameter measured by XRD is 80 nm or more and less than 160 nm, and the specific surface area measured by the BET method is 0.7 m or less. 2 / g or more 4.0m 2 / g or less.
[0047] Such a positive electrode active material can be prepared, for example, by appropriately adjusting the conditions of each step in the manufacturing method described later. For example, it is effective to use a titanium compound having an average particle size within a specific range in the mixing step (S10). Furthermore, the (003) crystallite size and the amount of lithium dissolved in water can be adjusted by performing the water washing step (S30) and drying step (S40) described later. Each metal element contained in the lithium nickel manganese composite oxide will be described below.
[0048] (lithium) In the above ratio of substance amounts (molar ratio), the range of a, which indicates the ratio of the substance amount of Li, is 0.97≦a≦1.25, preferably 1.00≦a≦1.15. When the range of a is within the above range, the reaction resistance of the positive electrode decreases and the output of the battery improves. When the value of a is less than 0.97 or exceeds 1.25, the reaction resistance increases and the output of the battery may decrease.
[0049] (manganese) In the above ratio of substance amounts (molar ratio), the range of x indicating the ratio of the substance amount of Mn to the substance amount of the contained metal element is 0.03≦x≦0.15, preferably 0.03≦x≦0.10. When the value of x is in the above range, high capacity and high thermal stability can be obtained. On the other hand, when the value of x is less than 0.03, the effect of improving thermal stability cannot be obtained. Also, when the value of x exceeds 0.15, the battery capacity decreases. Also, in the firing step (S20) described later, by including manganese, the firing temperature can be relatively high, and the dispersion of titanium and the like can be promoted. Note that, in the manufacturing method described later, even if the firing temperature is lowered, titanium can be dispersed throughout the positive electrode active material and solid-solved by appropriately adjusting other manufacturing conditions.
[0050] (Element M) In the above ratio of the amount of substance, the element M is at least one element selected from Co, V, Mg, Mo, Ca, Cr, Ta, Na, W, Fe, Zn, B, Si, P, Zr, Nb and Al. The range of y indicating the ratio of the amount of substance of the element M is 0≦y≦0.15. When y is 0 or more, it is possible to improve thermal stability, storage characteristics, and battery characteristics. When y exceeds 0.15, the structure becomes unstable, and a compound having a layered crystal structure may not be formed, or the battery capacity may decrease due to a relative decrease in the ratio of Ni and Mn. For example, when M contains Co, the battery capacity and output characteristics are more excellent. When M is Co, it is preferably 0≦y≦0.10. Furthermore, when the ratio of the amount of substance of Co contained in the element M is y1, it is preferably 0≦y1≦0.10, and more preferably 0.01≦y1≦0.10.
[0051] (titanium) In the above ratio of the amount of substance, the range of z, which indicates the amount of substance of Ti, is 0.01≦z≦0.05, preferably 0.01≦z≦0.03. When the range of z is within the above range, oxygen release can be suppressed and high thermal stability can be obtained when used in the positive electrode of a secondary battery. On the other hand, when the value of z is less than 0.01, the amount of titanium in solid solution is insufficient, so the effect of improving thermal stability is insufficient. In addition, when the value of z exceeds 0.05, the ratio of Ni and Mn is relatively reduced, and the crystal structure is unstable, which makes cation mixing more likely to occur, resulting in a significant decrease in battery capacity.
[0052] (nickel) In the above substance amount ratio, the lower limit of (1-xyz) showing the substance amount ratio of Ni is 0.65 or more, preferably 0.70 or more, more preferably 0.80 or more. When the substance amount ratio of nickel is in the above range, a secondary battery with high battery capacity can be obtained. When the substance amount ratio of nickel is high, the battery capacity is improved but the thermal stability may be reduced. However, the positive electrode active material according to the present embodiment has a specific amount of Ti with a specific distribution, and includes a water washing step (S30) and a drying step (S40), so that it can have very high thermal stability regardless of a high nickel ratio.
[0053] The composition of the lithium nickel manganese composite oxide can be measured by quantitative analysis using inductively coupled plasma (ICP) emission spectrometry.
[0054] (Titanium distribution) In the positive electrode active material according to the present embodiment, no or very weak diffraction peaks derived from a titanium-containing compound are detected in an XRD measurement, and a strong diffraction peak of a hexagonal layer structure is detected. That is, it is preferable that the titanium is almost entirely dissolved in the primary particles in the lithium nickel manganese composite oxide.
[0055] For example, when a lithium nickel manganese composite oxide containing titanium is produced without using the suitable production conditions described below, titanium may not be dissolved in the primary particles and may precipitate on the surfaces of the primary particles or on the grain boundaries between the primary particles. Examples of the form of titanium when it precipitates on the surfaces of the primary particles include TiO2 that remains as an unreacted product in the firing process derived from the titanium compound used as a raw material, and lithium titanate such as LiTiO2 that is produced by the reaction of a titanium compound with a lithium compound.
[0056] Here, the term "titanium is dissolved in the particles of the lithium nickel manganese composite oxide" refers to a state in which, for example, in an XRD measurement, no peak derived from the titanium compound containing TiO2, LiTiO2, or the like is detected, or even if detected, the peak is weak and does not substantially affect the battery characteristics of the obtained positive electrode active material.
[0057] Specifically, CuK α In the XRD measurement using the 1000 nm line, the (003) diffraction peak intensity (I (003) ) is the sum of the peak intensities of the strongest lines of titanium compounds (I Ti化合物 ) ratio (I Ti化合物 / I (003) (Hereinafter referred to as "peak intensity ratio") is preferably 0.2 or less, more preferably 0 or more and 0.1 or less, and may be 0. If the peak intensity ratio exceeds 0.2, a certain amount or more of titanium compound is precipitated, and the battery capacity may decrease. Note that, when each diffraction peak is below the detection limit, the diffraction peak intensity is set to 0 (zero).
[0058] For example, when TiO2 and LiTiO2 are detected as titanium compounds, the peak intensity ratio is the (003) diffraction peak intensity (I (003) ) versus the diffraction peak intensity of the strongest line of TiO2 (I TiO2 ) and the diffraction peak intensity of the strongest line of LiTiO2 (I LiTiO2 ) and the total amount [(I TiO2 +I LiTiO2 ) / I(003) ]
[0059] TiO2 has rutile and anatase types. Therefore, the intensity of the diffraction peak of TiO2 is the (110) diffraction peak intensity (I TiO2Rutile(110) ) and the integrated intensity (I TiO2Anatase(101) Here, the (110) diffraction peak position, which is the strongest line of rutile type TiO2, is 2θ = 27.9° (JCPDS number: 01-088-1175), and the (101) diffraction peak position, which is the strongest line of anatase type TiO2, is 2θ = 25.3° (JCPDS number: 01-084-1286).
[0060] In addition, when multiple lithium titanates having different compositions are simultaneously detected, the peak intensity of the strongest line of the lithium titanate is calculated as the sum of the strongest line peak intensities of each of the detected lithium titanates. Lithium titanates include, for example, LiTiO2, Li2TiO3, Li4TiO4, Li4Ti5O 12 etc.
[0061] In addition, when diffraction peaks of other titanium compounds (e.g., TiO, Ti2O3, TiC, etc.) are detected in the XRD measurement, the peak intensity ratio is I (003) For example, if TiO2, LiTiO2, and another titanium compound A are detected as titanium compounds, the peak intensity of the strongest line of titanium compound A is calculated as I チタン化合物A Then, the peak intensity ratio is [(I TiO2 +I LiTiO2 +I チタン化合物A ) / I (003) ]
[0062] [(003) crystallite size] The positive electrode active material according to this embodiment preferably has a crystallite diameter (hereinafter referred to as "(003) crystallite diameter") measured from the diffraction peak of the (003) plane derived from the hexagonal layer structure by XRD measurement of 80 nm or more and less than 160 nm, and may be 100 nm or more and less than 160 nm, 100 nm or more and 150 nm or less, or 100 nm or more and 140 nm or less. When the (003) crystallite diameter is in the above range, it is possible to suppress cracking of the positive electrode active material particles during repeated charging and discharging while having a high charge and discharge capacity, and to improve durability.
[0063] On the other hand, when the (003) crystallite diameter is 160 nm or more, the crystallinity is high and the discharge capacity is improved, but the expansion and contraction per primary particle during charging and discharging becomes large, so that particle cracking may easily occur during repeated charging and discharging. Also, when the (003) crystallite diameter is less than 80 nm, the crystallinity is low and the discharge capacity decreases. The (003) crystallite diameter can be set to the above range by appropriately adjusting the manufacturing conditions in the manufacturing method described later. As will be described in detail later, for example, by washing and drying the particles of lithium nickel manganese composite oxide obtained by firing, the crystallinity is improved and a higher discharge capacity can be obtained. Therefore, by setting the (003) crystallite diameter to the above range, it is possible to achieve a high level of both battery capacity and thermal stability and to have higher durability. The (003) crystallite diameter is calculated from the Scherrer formula using the half-width of the (003) diffraction peak derived from the hexagonal layered structure obtained by XRD measurement.
[0064] [Specific surface area] The positive electrode active material according to this embodiment has a specific surface area of 0.7 m as measured by the BET method. 2 / g or more 4.0m 2 / g or less. 2 When the specific surface area is set to 0.8 m / g or more, the number of reaction sites through which lithium ions can enter and exit increases, and the discharge capacity increases due to the reduction in the overvoltage at the end of discharge. 2 / g or more, 2 / g or more. Even when the positive electrode active material according to the present embodiment has a relatively large specific surface area, it is possible to achieve high thermal stability and high battery capacity by combining a specific titanium distribution and a specific crystallite size.
[0065] Although the details will be described later in the water washing step, by washing and drying the particles of the lithium nickel manganese composite oxide obtained by firing, the excess lithium component present on the particle surface and grain boundaries is eluted, and voids and unevenness are formed, thereby increasing the specific surface area. In addition to this, for example, in the crushing step of the fired product (agglomerates) after the firing step, the sintering and agglomeration are sufficiently broken down to adjust the specific surface area to the above range, thereby improving durability and obtaining a higher discharge capacity.
[0066] On the other hand, the positive electrode active material with a high nickel ratio has a specific surface area of 4.0 m 2 If the content exceeds 1 / g, even if the eluted alkaline components on the surface are removed once in the water washing step (S30), the alkaline components derived from lithium that react with moisture in the air and elute from the particle surface will increase, and when the positive electrode active material is made into a paste, the paste may gel, making it difficult to prepare an electrode plate.
[0067] [Variability index: [(D90-D10) / Mv]] In the positive electrode active material according to this embodiment, the particle size variation index [(D90-D10) / Mv], which is calculated from D90 and D10 (particle size at 90% and 10% of the volumetric accumulation of the particle amount in the particle size distribution curve) in the particle size distribution by the laser diffraction scattering method and the volume average particle size (Mv), is preferably 0.80 or more and 1.20 or less.
[0068] When the particle size distribution of the positive electrode active material is wide, there are many fine particles whose particle size is smaller than the average particle size and many coarse particles whose particle size is larger than the average particle size. If these fine particles and coarse particles are mixed, the packing density increases and the energy density per volume can be increased. Therefore, if the particle size variation index is less than 0.80, the volume energy density may decrease. If the manufacturing method described later is used, the upper limit is 1.20. If the firing temperature described later exceeds 950°C, the particle size variation index may exceed 1.20, but when the positive electrode active material is formed, the specific surface area decreases, the resistance of the positive electrode increases, and the battery capacity may decrease.
[0069] [Volume average particle size (Mv)] The positive electrode active material according to one embodiment of the present invention preferably has a volume average particle size (Mv) of 8 μm or more and 20 μm or less, and more preferably 10 μm or more and 20 μm or less. When the volume average particle size (Mv) is within the above range, when the positive electrode active material is used in the positive electrode of a secondary battery, it is possible to achieve both high output characteristics and battery capacity, as well as high packing properties into the positive electrode. If the average particle size of the secondary particles is less than 8 μm, high packing properties into the positive electrode may not be obtained, and if the average particle size exceeds 20 μm, high output characteristics and battery capacity may not be obtained. The average particle size can be determined, for example, from a volume integrated value measured by a laser diffraction scattering type particle size distribution analyzer.
[0070] [Lithium dissolution amount] In the positive electrode active material according to this embodiment, the amount of eluted lithium, which is the amount of lithium eluted into water when the positive electrode active material is immersed in water, is preferably 0.20% by mass or less, and may be 0.17% by mass or less, or may be 0.15% by mass or less, based on the total amount of the positive electrode active material. When the amount of eluted lithium is reduced by extracting lithium by stirring the water, and when the amount is within the above range, gelation is unlikely to occur during paste preparation, and defects due to gelation during battery plate preparation can be reduced. The lower limit of the amount of eluted lithium is not particularly limited, but in the positive electrode active material obtained by the manufacturing method described later, the lower limit of the amount of eluted lithium is, for example, 0.01% by mass or more, may be 0.05% by mass or more, or may be 0.08% by mass or more.
[0071] 2. Manufacturing method of positive electrode active material for lithium-ion secondary batteries Next, a method for producing a positive electrode active material for a lithium ion secondary battery according to one embodiment of the present invention (hereinafter, also referred to as a "positive electrode active material") will be described with reference to the drawings. Note that the following description is an example of the production method, and is not intended to limit the production method.
[0072] 4, 5(A) and 5(B) are process diagrams showing an outline of an example of a method for producing a positive electrode active material according to the present embodiment. As shown in Fig. 4, the method for producing a positive electrode active material includes at least a mixing step (S10) of mixing a nickel-manganese composite compound, a titanium compound and a lithium compound to obtain a mixture, a firing step (S20), a water-washing step (S30) and a drying step (S40). For example, as shown in Fig. 5(A) and (B), the nickel-manganese composite compound used in the mixing step (S10) may be obtained by a method including a crystallization step (S1) and / or a heat treatment step (S2).
[0073] The positive electrode active material obtained by the manufacturing method according to this embodiment has a high nickel ratio and contains specific amounts of manganese and titanium, and by dissolving titanium in a solid solution without precipitating an impurity phase, a high capacity can be obtained, and by containing manganese and titanium, short-circuit resistance and thermal stability can be improved. Furthermore, as described below, by providing a water washing step (S30), the disorder of the atomic arrangement of the lithium nickel manganese composite oxide is alleviated, and the specific surface area is increased by dissolving the excess lithium present on the particle surface and grain boundary, so that a higher battery capacity can be obtained. Each step will be described in detail below.
[0074] [Crystallization process (S1)] As shown in FIG. 5(A), the crystallization step (S1) is a step for obtaining a nickel-manganese composite hydroxide (nickel-manganese composite compound) by crystallization.
[0075] The nickel manganese composite hydroxide (hereinafter, sometimes referred to as "composite hydroxide") obtained in the crystallization step (S1) contains nickel (Ni), manganese (Mn), and element M (M), which is at least one element selected from Co, V, Mg, Mo, Ca, Cr, Ta, Na, W, Fe, Zn, B, Si, P, Zr, Nb, and Al, and the ratio of the amounts of substances (molar ratio) of each element is preferably expressed as Ni:Mn:M = 1-xy:x:y (where 0.03 ≦ x ≦ 0.15, 0 ≦ y ≦ 0.15). In addition, since the content (composition) of each element (Ni, Mn, M) in the nickel manganese composite hydroxide is almost maintained in the lithium nickel manganese composite oxide, the content of each element (Ni, Mn, M) is preferably in the same range as the content in the finally obtained lithium nickel manganese composite oxide.
[0076] The crystallization step (S1) can be performed by a known method as long as it can produce a composite hydroxide having the above-mentioned ratio of substance amounts. For example, in a reaction tank, a mixed aqueous solution containing at least nickel and manganese is stirred at a constant speed while a neutralizing agent is added to neutralize and control the pH, thereby producing a nickel-manganese composite hydroxide by co-precipitation.
[0077] The mixed aqueous solution containing nickel and manganese can be, for example, a sulfate solution, a nitrate solution, or a chloride solution of nickel and manganese. As described later, the mixed aqueous solution may also contain element M. The composition of each element contained in the mixed aqueous solution is almost the same as the composition of each element contained in the resulting composite hydroxide. Therefore, the composition of each element in the mixed aqueous solution can be adjusted to be the same as the composition of each element in the target composite hydroxide. The neutralizing agent can be an alkaline aqueous solution, for example, sodium hydroxide, potassium hydroxide, etc.
[0078] It is also preferable to add a complexing agent to the mixed aqueous solution together with the neutralizing agent. The complexing agent is not particularly limited as long as it can combine with nickel ions or other metal ions to form a complex in the aqueous solution in the reaction tank (hereinafter referred to as the "reaction aqueous solution"), and a known agent can be used, for example, an ammonium ion donor can be used. The ammonium ion donor is not particularly limited, but for example, ammonia, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride, etc. can be used. The addition of a complexing agent can adjust the solubility of metal ions in the reaction aqueous solution.
[0079] In the crystallization step (S1), when a complexing agent is not used, the temperature of the reaction aqueous solution (liquid temperature) is preferably in the range of more than 60°C to less than 80°C, and the pH of the reaction aqueous solution at the above temperature is preferably 10 to 12 (based on 25°C). If the pH of the reaction aqueous solution exceeds 12, the composite hydroxide obtained becomes fine particles, the filterability is also poor, and spherical particles may not be obtained. On the other hand, if the pH of the reaction aqueous solution is less than 10, the production rate of the composite hydroxide becomes significantly slow, Ni remains in the filtrate, and the amount of Ni precipitate deviates from the target composition, and the composite hydroxide with the target ratio may not be obtained.
[0080] In addition, when the temperature of the reaction aqueous solution exceeds 60°C, the solubility of Ni increases, the amount of Ni precipitate deviates from the target composition, and the phenomenon of no coprecipitation can be avoided. On the other hand, when the temperature of the reaction aqueous solution exceeds 80°C, the amount of water evaporated is large, so the slurry concentration (concentration of the reaction aqueous solution) increases, the solubility of Ni decreases, and crystals such as sodium sulfate are generated in the filtrate, increasing the impurity concentration, which may decrease the charge / discharge capacity of the positive electrode active material.
[0081] When an ammonium ion donor (complexing agent) is used in the crystallization step, the temperature of the reaction aqueous solution is preferably 30° C. or more and 60° C. or less because the solubility of Ni in the reaction aqueous solution increases, and the pH of the reaction aqueous solution is preferably 10 to 13 (based on 25° C.), more preferably 12 to 13.
[0082] In addition, the ammonia concentration in the reaction aqueous solution is preferably maintained at a constant value within the range of 3 g / L or more and 25 g / L or less. When the ammonia concentration is less than 3 g / L, the solubility of the metal ions cannot be maintained constant, so that primary particles of the composite hydroxide with a regular shape and particle size may not be formed. In addition, since gel-like nuclei are easily generated, the particle size distribution of the obtained composite hydroxide is likely to be broadened. On the other hand, when the ammonia concentration exceeds 25 g / L, the solubility of the metal ions becomes too large, the amount of metal ions remaining in the reaction aqueous solution increases, and the composition of the obtained composite hydroxide is likely to shift. In addition, since the solubility of the metal ions changes when the ammonia concentration fluctuates and uniform hydroxide particles are not formed, it is preferable to maintain the ammonia concentration at a constant value. For example, it is preferable to maintain the ammonia concentration at a desired concentration with the upper and lower limits being about 5 g / L.
[0083] The nickel manganese composite hydroxide may contain element M, which is at least one element selected from Co, V, Mg, Mo, Ca, Cr, Ta, Na, W, Fe, Zn, B, Si, P, Zr, Nb, and Al, as shown in the formula described later. The method for blending element M in the composite hydroxide is not particularly limited and any known method can be used. For example, from the viewpoint of increasing productivity, a method in which an aqueous solution containing element M is added to a mixed aqueous solution containing nickel and manganese, and a composite hydroxide containing element M is coprecipitated is preferred.
[0084] Examples of aqueous solutions containing the element M that can be used include aqueous solutions containing cobalt sulfate, vanadium oxychloride, vanadium oxysulfate, magnesium sulfate, magnesium chloride, molybdenum chloride, calcium chloride, chromium chloride, sodium tantalate, sodium hydroxide, sodium tungstate, tungsten oxide, iron sulfate, zinc chloride, zinc sulfate, boric acid, ammonium borate, silicon bromide, phosphoric acid, zirconium sulfate, zirconium nitrate, niobium hydroxide, niobium pentachloride, niobic acid, aluminum sulfate, and sodium aluminate.
[0085] From the viewpoint of optimizing the crystallization conditions and facilitating the control of the composition ratio, after obtaining composite hydroxide particles by crystallization, a step of coating the obtained composite hydroxide with element M may be further provided. The method of coating element M is not particularly limited, and a known method can be used.
[0086] An example of a coating method of element M will be described below. First, the nickel manganese composite hydroxide obtained by crystallization is dispersed in pure water to form a slurry. Next, a solution containing element M corresponding to the target coating amount is mixed with this slurry, and an acid or alkali is dropped to adjust the pH to a predetermined value. Examples of acids include sulfuric acid, hydrochloric acid, and nitric acid. Examples of alkalis include sodium hydroxide and potassium hydroxide. Next, the slurry is mixed for a predetermined time, and then filtered and dried to obtain a nickel manganese composite hydroxide coated with element M. Other coating methods include a spray-drying method in which a solution containing a compound containing element M is sprayed onto a nickel manganese composite hydroxide and then dried, and a method in which a solution containing a compound containing element M is impregnated into a nickel manganese composite hydroxide.
[0087] The method of incorporating the element M into the nickel-manganese composite hydroxide may include one or both of mixing the element M into the above-mentioned mixed aqueous solution and coating the composite hydroxide with the element M. For example, 1) an alkaline aqueous solution may be added to a mixed aqueous solution containing nickel and manganese (excluding the element M) to crystallize the nickel-manganese composite hydroxide, and the nickel-manganese composite hydroxide may be coated with the element M; 2) a mixed aqueous solution containing nickel, manganese and a portion of the element M may be prepared, and the nickel-manganese composite hydroxide (containing the element M) may be coprecipitated, and the coprecipitate may be further coated with the element M to adjust the content of M.
[0088] The crystallization step (S1) may be 1) a batch crystallization method (batch crystallization method) or 2) a continuous crystallization method (continuous crystallization method). For example, in the case of the batch crystallization method, after the reaction aqueous solution in the reaction tank reaches a steady state, the precipitate is collected, filtered, and washed with water to obtain a composite hydroxide. In the case of the continuous crystallization method, the mixed aqueous solution, the alkaline aqueous solution, and in some cases an aqueous solution containing an ammonium ion donor are continuously supplied to overflow the reaction tank, and the precipitate is collected, filtered, and washed with water to obtain a composite hydroxide.
[0089] In the method for producing a positive electrode active material according to the present embodiment, it is preferable to use a continuous crystallization method from the viewpoint of obtaining a positive electrode active material that exhibits a high volumetric energy density when used in a secondary battery. In the production by continuous crystallization, a positive electrode active material having a high variation index, a broad particle size distribution width, and high packing property can be easily obtained. In addition, the continuous crystallization method is more productive than batch crystallization and is suitable for production on an industrial scale.
[0090] [Heat treatment process (S2)] As shown in Fig. 5(B), the composite hydroxide obtained by the crystallization step (S1) may be further subjected to a heat treatment step (S2). The heat treatment step (S2) is a step of removing at least a part of the moisture contained in the composite hydroxide by heat treatment. By including the heat treatment step (S2), at least a part of the moisture remaining in the composite hydroxide can be removed, thereby preventing variation in Li / Me of the positive electrode active material obtained in the firing step (S20) described later.
[0091] From the viewpoint of further reducing the variation in Li / Me, the heat treatment in the heat treatment step (S2) is preferably performed so as to sufficiently oxidize the composite hydroxide and convert it into composite oxide particles. Note that it is not necessary to convert all of the hydroxides (composite hydroxides) in the composite hydroxide into composite oxides, as long as the moisture can be removed to an extent that does not cause variation in Li / Me in the positive electrode active material. In other words, by heat treating the composite hydroxide, a nickel-manganese composite compound containing at least one of a nickel-manganese composite hydroxide and a nickel-manganese composite oxide can be obtained.
[0092] In addition, when the heat treatment step (S2) is performed, the nickel manganese composite compound obtained by the heat treatment step (S2) may be used in the mixing step (S10) as shown in Fig. 5(B). In addition, when the composite hydroxide contains the element M, the heat treatment step (S2) may be performed after the composite hydroxide is coated with a compound containing the element M, or the composite hydroxide and / or composite oxide particles after the heat treatment step (S2) may be coated with a compound containing the element M.
[0093] The heat treatment in the heat treatment step (S2) may be performed by heating to a temperature at which the residual moisture in the composite hydroxide is removed. For example, the heat treatment temperature is preferably 105°C or higher and 700°C or lower. When the composite hydroxide is heated to 105°C or higher, at least a part of the residual moisture can be removed. If the heat treatment temperature is lower than 105°C, it takes a long time to remove the residual moisture, which is not industrially appropriate. On the other hand, if the heat treatment temperature exceeds 700°C, the particles converted into composite oxide particles may sinter and aggregate. For example, when most of the composite hydroxide is converted into composite oxide particles, the heat treatment temperature is preferably 350°C or higher and 700°C or lower.
[0094] The atmosphere in which the heat treatment is carried out is not particularly limited, and from the viewpoint of easy operation, for example, it is preferable to carry out the heat treatment in an air stream. The time of the heat treatment is not particularly limited, and can be, for example, 1 hour or more. If the time of the heat treatment is less than 1 hour, the residual moisture in the composite hydroxide may not be sufficiently removed. The time of the heat treatment is preferably 5 hours or more and 15 hours or less. The equipment used for the heat treatment is not particularly limited, and it is sufficient if it can heat the composite hydroxide in an air stream, and for example, a blower dryer, an electric furnace that does not generate gas, etc. can be suitably used.
[0095] 5(B), the nickel-manganese composite hydroxide after the crystallization step (S1) is heat-treated, but a nickel-manganese composite hydroxide obtained in a step other than the crystallization step (S1) may be heat-treated and used as a nickel-manganese composite compound in the mixing step (S10). Even in this case, the above-mentioned effect can be obtained by removing at least a part of the moisture in the nickel-manganese composite hydroxide.
[0096] [Mixing process (S10)] The nickel manganese composite compound used in the mixing step (S10) contains, as metal elements, nickel (Ni), manganese (Mn), and, optionally, an element M (M) which is at least one element selected from Co, V, Mg, Mo, Ca, Cr, Ta, Na, W, Fe, Zn, B, Si, P, Zr, Nb, and Al, and the ratio of the amounts of substance of these metal elements is expressed as Ni:Mn:M=1-xy:x:y (where 0.03≦x≦0.15, 0≦y≦0.15).
[0097] The content (composition) of each element (Ni, Mn, M) in the nickel manganese composite compound is almost maintained in the lithium nickel manganese composite oxide particles, so the content of each element (Ni, Mn, element M) is preferably in the same range as the content in the lithium nickel manganese composite oxide described above. Note that the nickel manganese composite compound used in this embodiment may contain small amounts of elements other than the above-mentioned elements (Ni, Mn, element M), hydrogen, and oxygen as long as the effects of the present invention are not impaired.
[0098] By containing manganese in the above range, the nickel-manganese composite compound can distribute manganese uniformly within the multiple primary particles of the resulting positive electrode active material. The positive electrode active material in which manganese and titanium are contained (solid solution) within the multiple primary particles has high thermal stability, and the volume resistivity is increased, improving short-circuit resistance.
[0099] Furthermore, since the primary particles contain manganese, the lithium-titanium mixture can be sintered at a relatively high temperature, and the high temperature sintering allows the titanium in the titanium compound to be more uniformly dissolved in the primary particles.
[0100] Although the method for producing the nickel-manganese composite compound is not particularly limited, it is preferable to use a composite hydroxide and / or composite oxide obtained by a crystallization step (S1) and / or a heat treatment step (S2) as shown in Figures 5(A) and 5(B), and it is more preferable to use a nickel-manganese composite hydroxide obtained by the crystallization step (S1). This makes it possible to easily obtain a lithium-nickel-manganese composite oxide in which titanium is dissolved in the primary particles in the firing step (S20) described later.
[0101] In addition, it is preferable that nickel and manganese are uniformly contained in the nickel manganese composite compound. For example, when a mixture of nickel hydroxide particles and a manganese compound separately mixed, or nickel hydroxide particles coated with a manganese compound, is used as a raw material, the distribution of manganese in the obtained positive electrode active material becomes non-uniform, and the effect obtained by including manganese may not be sufficiently obtained.
[0102] (Titanium compounds) As the titanium compound used in the mixing step (S10), a known compound containing titanium can be used, such as titanium oxide, titanium sulfate, titanium tetrabromide, titanium tetrachloride, titanium silicide, etc. One type of titanium compound may be used, or two or more types may be used.
[0103] Among these, titanium oxide is preferred from the viewpoints of availability and avoiding impurities from being mixed into the lithium nickel manganese composite oxide. If impurities are mixed into the lithium nickel manganese composite oxide, the thermal stability, battery capacity, and cycle characteristics of the resulting secondary battery may be reduced.
[0104] The titanium compound is preferably mixed in the form of particles (solid phase). When titanium is added in the solid phase, the particle size of the titanium compound used is one of the important factors because the reactivity in the subsequent firing step (S20) changes depending on the particle size of the titanium compound.
[0105] The average particle size of the titanium compound is preferably 0.01 μm or more and 5 μm or less, more preferably 0.05 μm or more and 3 μm or less, and even more preferably 0.08 μm or more and 3 μm or less. If the average particle size is smaller than 0.01 μm, there may be a problem that the powder is very difficult to handle, or that the titanium compound scatters in the mixing step (S10) and the firing step (S20), and the intended composition cannot be added to the active material. On the other hand, if the average particle size is larger than 5 μm, titanium may not be uniformly distributed in the lithium nickel manganese composite oxide after firing, and the battery capacity may decrease. The average particle size is the volume average particle size Mv, and can be obtained, for example, from the volume integrated value measured by a laser diffraction scattering type particle size distribution meter.
[0106] The titanium compound may be ground in advance to a particle size within the above range using various grinding machines such as a ball mill, a planetary ball mill, a jet mill, a nanojet mill, a bead mill, and a pin mill. The titanium compound may also be classified by a dry classifier or sieving, if necessary. For example, particles close to 1 μm can be obtained using a dry classifier.
[0107] (Lithium compounds) The lithium compound is not particularly limited, and any known compound containing lithium can be used, such as lithium carbonate, lithium hydroxide, lithium nitrate, or a mixture thereof. Among these, lithium carbonate, lithium hydroxide, or a mixture thereof is preferred from the viewpoints of being less affected by residual impurities and dissolving at the firing temperature.
[0108] (Mixing method) The method of mixing the nickel manganese composite compound, the lithium compound, and the titanium compound is not particularly limited, and the composite hydroxide, the lithium compound, and the titanium compound may be mixed sufficiently to the extent that the form of the composite hydroxide is not destroyed. As a mixing method, for example, a general mixer can be used, for example, a shaker mixer, a Loedige mixer, a Julia mixer, a V blender, etc. can be used. It is preferable to mix the lithium titanium mixture sufficiently before the firing process described later. If the mixing is not sufficient, the ratio of the amount of substance of Li and the element Me other than Li (i.e., Ni + Mn + element M + Ti) (Li / Me, corresponding to a in the amount of substance ratio described later, atomic % ratio) varies between individual particles of the positive electrode active material, and problems such as insufficient battery characteristics can occur.
[0109] The lithium compounds are mixed so that the Li / Me ratio in the lithium titanium mixture is 0.97 or more and 1.25 or less. That is, the lithium titanium mixture is mixed so that the Li / Me ratio is the same as the Li / Me ratio in the resulting positive electrode active material. This is because the Li / Me ratio and the molar ratio of each metal element do not change before and after the firing step (S20) described later, so that the Li / Me ratio of the lithium titanium mixture at the time of the above mixing is the Li / Me ratio of the positive electrode active material. In addition, for example, by adjusting the value of Li / Me ratio in the mixture, the crystallite size of the lithium nickel manganese composite oxide obtained after firing can be adjusted.
[0110] The titanium compound is mixed so that the ratio (Ti / Me) of the amount of titanium (Ti) in the lithium titanium mixture to the total of the metal elements other than Li in the lithium titanium mixture (Ni, Mn, element M, Ti) is 0.01 or more and 0.05 or less.
[0111] [Firing process (S20)] The firing step (S20) is a step of firing the lithium-titanium mixture obtained in the mixing step (S10) at a temperature of 700°C or higher and 950°C or lower in an oxidizing atmosphere with an oxygen concentration of 80% by volume or higher and 100% by volume or lower to obtain a lithium-nickel-manganese composite oxide.
[0112] When the lithium-titanium mixture is fired, the lithium in the lithium compound diffuses into the particles of the nickel-manganese composite compound, forming lithium-nickel-manganese composite oxide particles (secondary particles) consisting of particles with a polycrystalline structure. The lithium compound melts at the firing temperature and penetrates into the particles of the nickel-manganese composite compound to form a lithium-nickel-manganese composite oxide. At this time, the titanium compound penetrates into the inside of the secondary particles together with the molten lithium compound. Also, if there is a crystal grain boundary in the primary particles, it penetrates. The penetration of the lithium compound and the titanium compound promotes diffusion inside the primary particles, and titanium is uniformly dissolved in the primary particles. As a result of the study by the present inventors, for example, by controlling the oxygen concentration in the firing atmosphere and the firing temperature, titanium is uniformly dissolved in the inside of the primary particles, and precipitation as a titanium compound phase and segregation to the interface between the primary particles are suppressed.
[0113] The firing atmosphere has an oxygen concentration of 80% by volume or more and 100% by volume or less, and preferably an oxygen concentration of 90% by volume or more and 100% by volume or less. A lithium nickel manganese composite oxide with a high nickel ratio is prone to so-called cation mixing, in which transition metal elements such as Ni are arranged at the Li site in the layered compound. In addition, the crystallinity of the layered compound is reduced, and the atomic distribution is prone to be disturbed. Due to these structural disturbances, titanium cannot be dissolved in the Me site (transition metal site) and precipitates as an impurity phase (heterogeneous phase) of titanium compounds, etc., which may reduce the battery capacity. On the other hand, when firing is performed within the above oxygen concentration range, the phase transition of the lithium nickel manganese composite oxide to the layered compound is promoted, and titanium is easily dissolved in the transition metal site in the layered compound. Therefore, even within the above titanium content range, titanium can be uniformly dissolved in the primary particles without precipitating the impurity phase. As a result, it is possible to obtain a positive electrode active material that improves the battery capacity and reduces the volume resistivity while maintaining high thermal stability, thereby achieving both battery characteristics, short-circuit resistance, and thermal stability.
[0114] The firing temperature is 700°C to 950°C in an oxidizing atmosphere, preferably 700°C to 900°C, and may be 750°C to 850°C. When firing at the above temperature, the lithium compound melts, and the penetration and diffusion of titanium are promoted. In addition, the lithium titanium mixture can be fired at a high temperature by containing manganese. By increasing the firing temperature, the diffusion of titanium is promoted, and titanium is easily dissolved in the particles of the lithium nickel manganese composite oxide, so that both high thermal stability and high battery capacity can be achieved. In addition, in the water washing and drying steps (S30, S40) described later, the crystallite diameter of the lithium nickel manganese composite oxide finally obtained can be adjusted by appropriately adjusting the firing temperature within the above range, taking into account the increase in the (003) plane crystallite diameter.
[0115] On the other hand, if the sintering temperature is less than 700°C, the diffusion of lithium and titanium into the composite hydroxide is not sufficient, and excess lithium and unreacted particles remain, or the crystal structure is not fully aligned, resulting in a problem that sufficient battery characteristics cannot be obtained. In addition, the solid solution of titanium into the primary particles is insufficient, and sufficient short-circuit resistance and thermal stability may not be obtained. Furthermore, if the sintering temperature exceeds 950°C, intense sintering may occur between the particles of the formed lithium nickel manganese composite oxide, and abnormal grain growth may occur. If abnormal grain growth occurs, the particles after sintering become coarse, and when the positive electrode active material is formed, the packing property is reduced, and the reaction resistance increases due to the disturbance of the crystal structure, resulting in a problem of a decrease in discharge capacity.
[0116] The calcination time is preferably at least 3 hours, more preferably 6 hours to 24 hours. If the calcination time is less than 3 hours, the lithium nickel manganese composite oxide may not be sufficiently produced. The furnace used for calcination is not particularly limited as long as it can calcinate the lithium titanium mixture in an oxygen stream, but it is preferable to use an electric furnace that does not generate gas, and either a batch type or a continuous type furnace can be used.
[0117] [Pre-firing] The calcination step may further include a step of calcining at a temperature lower than the calcination temperature before calcining at a temperature of 700°C or more and 950°C or less. The calcination is preferably performed at a temperature at which the lithium compound in the lithium-titanium mixture can melt and react with the composite hydroxide. The calcination temperature can be, for example, 350°C or more and lower than the calcination temperature. The lower limit of the calcination temperature is preferably 400°C or more. By holding (calcining) the lithium-titanium mixture in the above temperature range, the lithium compound and / or titanium compound penetrate into the particles of the nickel-manganese composite compound, and lithium and titanium are sufficiently diffused, so that a uniform lithium-nickel-manganese composite oxide can be obtained. For example, when lithium hydroxide is used as the lithium compound, the calcination is preferably performed by holding at a temperature of 400°C or more and 550°C or less for about 1 hour to 10 hours.
[0118] [Crushing] In the lithium nickel manganese composite oxide obtained after the firing step (S20), sintering between particles is suppressed, but coarse particles may be formed due to weak sintering or aggregation. In such cases, the particle size distribution can be adjusted by eliminating the sintering or aggregation through crushing. Although the crushing method is not particularly limited, the specific surface area of the lithium nickel manganese composite oxide can be increased by sufficiently loosening the sintering and aggregation through crushing.
[0119] [Water washing process (S30)] The water washing step (S30) is a step in which the lithium nickel manganese composite oxide obtained in the firing step (S20) is mixed with water and stirred (hereinafter referred to as "water stirring"), followed by solid-liquid separation.
[0120] The manufacturing method according to the present embodiment includes a water washing step (S30) and a drying step (S40) described later, which reduces the disorder of the atomic arrangement of the positive electrode active material and improves the crystallinity. Furthermore, the specific surface area increases as the excess lithium present on the particle surface and grain boundaries of the lithium nickel manganese composite oxide dissolves into water. Although the details are unclear, it is believed that these effects reduce the overvoltage during discharge, thereby improving the discharge capacity.
[0121] As described above, if titanium is not contained in the positive electrode active material, the crystallinity is not improved, and the specific surface area increases, but the reaction resistance increases, so that the discharge capacity does not increase even if the positive electrode active material is washed with water. Although the details of the cause are unclear, in the positive electrode active material according to this embodiment, the titanium dissolved in the primary particles may have the effect of suppressing the deterioration of the particle surface and grain boundaries due to the elution of lithium. In addition, the water washing step (S30) dissolves and removes the excess lithium component on the surface in water, thereby suppressing the gelation of the positive electrode composite paste during the manufacture of the electrode plate of the secondary battery.
[0122] The amount of water mixed in the water washing step (S30) is preferably 50 parts by mass or more and 200 parts by mass or less per 100 parts by mass of the lithium nickel manganese composite oxide. If the mixing ratio of water is 200 parts by mass or more, an excessive amount of lithium is extracted from the positive electrode active material, which may cause a decrease in battery capacity and an increase in reaction resistance. On the other hand, if the mixing ratio of water is less than 50 parts by mass, the effect of improving crystallinity and the removal of excess lithium components may be insufficient, which may cause a decrease in battery capacity and gelation of the positive electrode composite paste.
[0123] The time for washing with water is not particularly limited, but may be, for example, from 1 minute to 2 hours, and may be from 5 minutes to 50 minutes.
[0124] The lithium nickel manganese composite oxide is stirred with water, and then subjected to solid-liquid separation to obtain a lithium nickel manganese composite oxide (precipitate). The method of solid-liquid separation is not particularly limited, and a known method can be used. For example, solid-liquid separation can be performed using one or more types selected from a suction filter such as a Nutsche (Buchner funnel), a filter press, a centrifuge, and the like.
[0125] [Drying process (S40)] The drying step (S40) is a step of drying the lithium nickel manganese composite oxide (precipitate) obtained in the water washing step (S30) to obtain a lithium metal composite oxide powder (dry powder).
[0126] The drying conditions are preferably a heat treatment at a temperature of 100° C. to 250° C. in an oxidizing atmosphere or a vacuum atmosphere. When the drying temperature is 100° C. or higher, the moisture in the precipitate can be sufficiently evaporated. When the drying temperature is 250° C. or lower, a compact drying device can be used, which is suitable for implementation on an industrial scale.
[0127] The atmosphere during drying is preferably an atmosphere that does not contain water vapor or carbon dioxide in order to avoid a reaction between the moisture or carbon dioxide in the atmosphere and the resulting positive electrode active material, and specifically, an oxidizing atmosphere such as an oxygen atmosphere or a vacuum atmosphere is preferable. In addition, from the viewpoint of being able to quickly exhaust water vapor generated by drying, it is preferable to add an exhaust mechanism to the drying device.
[0128] The drying time is not particularly limited, but is preferably 0.5 hours or more at the maximum temperature reached during drying in order to sufficiently evaporate the moisture in the raw material mixture, and the upper limit of the drying time is preferably 48 hours or less from the viewpoint of productivity.
[0129] [Cathode active material] The positive electrode active material obtained by the manufacturing method according to this embodiment can achieve both high battery characteristics and high thermal stability at a high level when used in the positive electrode of a lithium ion secondary battery. Moreover, the manufacturing method according to this embodiment can easily manufacture such a positive electrode active material in industrial-scale production, and it can be said that the industrial value is extremely great.
[0130] In addition, the (003) crystallite diameter of the lithium nickel manganese composite oxide (positive electrode active material) obtained after the drying step (S40) is increased compared to the (003) crystallite diameter of the lithium nickel manganese composite oxide obtained after the firing step (S20) and before the water washing step (S30). The (003) crystallite diameter of the obtained positive electrode active material may increase, for example, by 15 nm or more, or may increase by 20 nm or more compared to before the water washing step (S30). When the (003) crystallite diameter increases after the water washing step (S30), the battery capacity can be improved when the obtained positive electrode active material is used in a secondary battery. The details of the reason for this are not clear, but it is considered that, for example, when lithium is extracted from the lithium nickel manganese composite oxide by the water washing step (S30), the disorder of the atomic arrangement is alleviated, so that the diffraction peak of the XRD measurement becomes sharp and the crystallite diameter appears to increase. Moreover, the increase in the (003) crystallite size is particularly noticeable in lithium nickel manganese composite oxides containing a specific amount of titanium.
[0131] 3. Lithium-ion secondary battery The lithium ion secondary battery according to this embodiment (hereinafter, also referred to as "secondary battery") comprises a positive electrode containing the above-mentioned positive electrode active material, a negative electrode, and a non-aqueous electrolyte. The secondary battery comprises, for example, a positive electrode, a negative electrode, and a non-aqueous electrolyte. The secondary battery may also comprise, for example, a positive electrode, a negative electrode, and a solid electrolyte. The secondary battery may be a secondary battery that performs charging and discharging by desorption and insertion of lithium ions, and may be, for example, a non-aqueous electrolyte secondary battery or an all-solid-state lithium secondary battery. Note that the embodiments described below are merely illustrative, and the lithium ion secondary battery may be implemented in various forms that have been modified and improved based on the knowledge of a person skilled in the art, including the following embodiments. The secondary battery is not particularly limited in its use.
[0132] [Positive electrode] The positive electrode of the secondary battery is produced using the above-mentioned positive electrode active material. An example of a method for producing the positive electrode will be described below.
[0133] First, the above-mentioned positive electrode active material (powder), conductive material, and binder are mixed, and activated carbon and a solvent for the purpose of viscosity adjustment, etc. are added as necessary, and the mixture is kneaded to prepare a positive electrode mixture paste.
[0134] The mixing ratio of each material in the positive electrode mixture is a factor that determines the performance of the lithium ion secondary battery, and can be adjusted depending on the application. The mixing ratio of the materials can be the same as that of the positive electrode of a known lithium secondary battery, and for example, when the total mass of the solid content of the positive electrode mixture excluding the solvent is taken as 100 mass%, the positive electrode mixture can contain 60 to 95 mass% of the positive electrode active material, 1 to 20 mass% of the conductive material, and 1 to 20 mass% of the binder.
[0135] The obtained positive electrode composite paste is applied to the surface of a current collector made of, for example, aluminum foil, and dried to remove the solvent, thereby producing a sheet-like positive electrode. If necessary, pressure may be applied by a roll press or the like to increase the electrode density. The sheet-like positive electrode thus obtained can be cut to an appropriate size according to the desired battery and used for the production of the battery. However, the method of producing the positive electrode is not limited to the above-mentioned example, and other methods may be used.
[0136] As the conductive material, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.) and carbon black-based materials such as acetylene black and ketjen black can be used.
[0137] The binder serves to bind the active material particles together, and examples of the binder that can be used include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose-based resins, and polyacrylic acid.
[0138] If necessary, a solvent that disperses the positive electrode active material, conductive material, and activated carbon and dissolves the binder is added to the positive electrode mixture. Specifically, an organic solvent such as N-methyl-2-pyrrolidone can be used as the solvent. Activated carbon can also be added to the positive electrode mixture to increase the electric double layer capacity.
[0139] [Negative electrode] The negative electrode may be made of metallic lithium, a lithium alloy, etc. Alternatively, the negative electrode may be made by mixing a binder with a negative electrode active material capable of absorbing and desorbing lithium ions, adding an appropriate solvent to make a paste-like negative electrode mixture, applying the paste to the surface of a metal foil current collector such as copper, drying it, and compressing it to increase the electrode density as necessary.
[0140] As the negative electrode active material, for example, natural graphite, artificial graphite, sintered organic compounds such as phenol resin, and powder of carbon material such as coke can be used. In this case, as with the positive electrode, fluorine-containing resin such as PVDF can be used as the negative electrode binder, and an organic solvent such as N-methyl-2-pyrrolidone can be used as the solvent for dispersing these active materials and binders.
[0141] [Separator] A separator is sandwiched between the positive electrode and the negative electrode. The separator separates the positive electrode and the negative electrode and holds the electrolyte. Any known separator can be used, for example, a thin membrane made of polyethylene or polypropylene having many minute pores.
[0142] [Non-aqueous electrolyte] As the non-aqueous electrolyte, for example, a non-aqueous electrolytic solution can be used. The non-aqueous electrolyte solution is a solution in which a lithium salt as a supporting salt is dissolved in an organic solvent. Alternatively, a solution in which a lithium salt is dissolved in an ionic liquid may be used as the non-aqueous electrolyte solution. The ionic liquid refers to a salt that is composed of cations and anions other than lithium ions and is liquid even at room temperature.
[0143] The organic solvent may be one selected from the group consisting of cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate; ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane; sulfur compounds such as ethyl methyl sulfone and butane sultone; and phosphorus compounds such as triethyl phosphate and trioctyl phosphate. The organic solvent may be one selected from the group consisting of cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and trifluoropropylene ...
[0144] The supporting salt may be LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, or a composite salt thereof. Furthermore, the non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant, and the like.
[0145] The non-aqueous electrolyte may be a solid electrolyte. The solid electrolyte has a property of being able to withstand high voltage. Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes.
[0146] Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes.
[0147] The oxide-based solid electrolyte is not particularly limited, and for example, an oxide-based solid electrolyte containing oxygen (O) and having lithium ion conductivity and electronic insulation can be suitably used. Examples of the oxide-based solid electrolyte include lithium phosphate (Li3PO4), Li3PO4N X , LiBON X , LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≦X≦1), Li 1+X Al X Ge 2-X (PO4)3(0≦X≦1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3(0≦X≦2 / 3), Li5La3Ta2O 12 , Li7La3Zr2O 12 , Li6BaLa2Ta2O 12 , Li 3.6 S 0.6 P 0.4 One or more types selected from O4, etc. can be used.
[0148] The sulfide-based solid electrolyte is not particularly limited, and for example, one containing sulfur (S) and having lithium ion conductivity and electronic insulation can be suitably used. For example, the sulfide-based solid electrolyte can be one or more selected from Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc.
[0149] As the inorganic solid electrolyte, materials other than those mentioned above may be used, for example, Li3N, LiI, Li3N-LiI-LiOH, etc. may be used.
[0150] The organic solid electrolyte is not particularly limited as long as it is a polymer compound exhibiting ion conductivity, and examples of the organic solid electrolyte that can be used include polyethylene oxide, polypropylene oxide, copolymers thereof, etc. The organic solid electrolyte may also contain a supporting salt (lithium salt).
[0151] It is also possible to construct a secondary battery using a solid electrolyte instead of a non-aqueous electrolyte. The solid electrolyte does not decompose even at high potentials, and therefore has high thermal stability because there is no gas generation or thermal runaway caused by the decomposition of the electrolyte during charging as seen in non-aqueous electrolytes. Therefore, when used in a lithium ion secondary battery using the positive electrode active material according to the present invention, a secondary battery with higher thermal stability can be obtained.
[0152] [Shape and composition of secondary batteries] The configuration of the secondary battery is not particularly limited, and may be composed of a positive electrode, a negative electrode, a separator, a non-aqueous electrolyte, etc. as described above, or may be composed of a positive electrode, a negative electrode, a solid electrolyte, etc. The shape of the secondary battery is not particularly limited, and may be various shapes such as a cylindrical shape or a laminated shape.
[0153] For example, when the secondary battery is a non-aqueous electrolyte secondary battery, a positive electrode and a negative electrode are laminated with a separator interposed therebetween to form an electrode body, the obtained electrode body is impregnated with a non-aqueous electrolyte, the positive electrode current collector and a positive electrode terminal connected to the outside, and the negative electrode current collector and a negative electrode terminal connected to the outside are connected using a current collecting lead or the like, and the battery is sealed in a battery case to complete the secondary battery.
[0154] The secondary battery according to the present embodiment is not limited to a battery using a non-aqueous electrolyte solution as a non-aqueous electrolyte, and may be, for example, a secondary battery using a solid non-aqueous electrolyte, i.e., an all-solid-state battery. In the case of an all-solid-state battery, the configuration other than the positive electrode active material may be changed as necessary.
[0155] The secondary battery according to this embodiment can achieve high thermal stability at low cost. The positive electrode active material used in the secondary battery can be obtained by the above-mentioned industrial manufacturing method. The secondary battery is suitable as a power source for small portable electronic devices (such as notebook personal computers and mobile phone terminals) that always require high capacity. The secondary battery is also superior in not only capacity but also durability and thermal stability during overcharging, compared with batteries using conventional lithium cobalt oxide or lithium nickel oxide positive electrode active materials. Therefore, since it is possible to reduce the size and increase the capacity, it is suitable as a power source for electric vehicles that are limited by the mounting space. The secondary battery can be used not only as a power source for electric vehicles that are driven purely by electrical energy, but also as a power source for so-called hybrid vehicles that are used in combination with combustion engines such as gasoline engines and diesel engines. EXAMPLES
[0156] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. The various evaluation methods for the positive electrode active material in the examples and comparative examples are as follows.
[0157] (A) Composition analysis: Measured by ICP atomic emission spectrometry.
[0158] (B) Qualitative evaluation of crystal structure and the presence or absence of impurity phases, and calculation of the (003) crystallite size: The XRD diffraction pattern was evaluated using Cu-Kα radiation with an XRD diffractometer (X'Pert PRO, manufactured by PANalytical Co., Ltd.) under the following measurement conditions: output 45 kV, 40 mA, step size: 0.0168°, scan speed: 0.0508° / sec.
[0159] From the diffraction pattern, the presence or absence of other phases other than the hexagonal layer structure and the peak intensity ratio (I Ti化合物 / I (003) ) was obtained. Note that the peaks below the detection limit were calculated as having a peak intensity of 0. Specifically, in the comparative example described later, when LiTiO2 was detected as a Ti compound, the (200) diffraction peak intensity I LiTiO2 Using the above, the peak intensity ratio (I LiTiO2 / I (003) Here, the (200) diffraction peak position, which is the strongest line of LiTiO2, is located near 2θ = 43.7°, and the (003) diffraction peak position, which is the strongest line of the hexagonal layered structure, is located near 2θ = 18.7°.
[0160] In addition, the (003) crystallite size was calculated from the (003) half-width of the obtained hexagonal layered structure by the Scherrer formula.
[0161] (C) Amount of eluted lithium: 20 g of the positive electrode active material was taken and placed in 100 ml of pure water at 25°C, immersed and stirred for 30 minutes, and the supernatant liquid after standing for 10 minutes was titrated using an aqueous HCl solution. The titration was evaluated by the Warder method, and the amounts of lithium hydroxide (LiOH) and lithium carbonate (Li2CO3) were calculated, and the sum of these amounts of lithium was calculated as the amount of eluted lithium.
[0162] (D) Volume average particle size Mv, and particle size variation index [(D90-D10) / volume average particle size Mv]: The measurement was performed on a volume basis using a laser diffraction scattering type particle size distribution measuring device (Microtrack HRA, manufactured by Nikkiso Co., Ltd.).
[0163] (E) Specific surface area: Measured by the BET method using nitrogen adsorption using a specific surface area / pore distribution measuring device (Mountec Co., Ltd., Model: Maxsorb HM1200 Series).
[0164] (F) Initial charge capacity and initial discharge capacity: The initial charge capacity and initial discharge capacity were measured by leaving the 2032-type coin cell CBA shown in FIG. 6 for about 24 hours after preparation, and after the open circuit voltage OCV stabilized, applying a current density of 0.1 mA / cm to the positive electrode. 2 The initial charge capacity was determined by charging the battery to a cut-off voltage of 4.3 V, and after one hour of rest, the initial discharge capacity was determined by discharging the battery to a cut-off voltage of 3.0 V. A multi-channel voltage / current generator (R6741A, manufactured by Advantest Corporation) was used to measure the discharge capacity.
[0165] The coin-type battery CBA was prepared by mixing 52.5 mg of the positive electrode active material, 15 mg of acetylene black, and 7.5 mg of polytetrafluoroethylene resin (PTFE), and pressing the mixture at a pressure of 100 MPa to a diameter of 11 mm and a thickness of 100 μm to prepare a positive electrode (electrode for evaluation) PE. The prepared positive electrode PE was dried in a vacuum dryer at 120°C for 12 hours, and then the coin-type battery CBA was prepared using this positive electrode PE in a glove box in an Ar atmosphere with a dew point controlled at -80°C.
[0166] The negative electrode NE was made of lithium (Li) metal with a diameter of 17 mm and a thickness of 1 mm, and the electrolyte was an equal mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) (manufactured by Toyama Pharmaceutical Co., Ltd.) with 1M LiClO4 as the supporting electrolyte. The separator SE was made of a polyethylene porous film with a thickness of 25 μm. The coin-type battery had a gasket GA and a wave washer WW, and was assembled into a coin-type battery with a positive electrode can PC and a negative electrode can NC.
[0167] (G) Thermal stability evaluation The thermal stability of the positive electrode was evaluated by quantifying the amount of oxygen released by heating the positive electrode active material in an overcharged state. A coin-type battery CBA was prepared in the same manner as in (E) and CC-charged (constant current-constant voltage) at a rate of 0.05C up to a cutoff voltage of 4.3V. The coin-type battery CBA was then disassembled, and the positive electrode was carefully removed to avoid short-circuiting, washed with DMC (dimethyl carbonate), and dried. Approximately 2 mg of the dried positive electrode was weighed and heated from room temperature to 450°C at a heating rate of 10°C / min using a gas chromatograph mass spectrometer (GCMS, Shimadzu Corporation, QP-2010plus). Helium was used as the carrier gas. The generation behavior of oxygen (m / z=32) generated during heating was measured, and the amount of oxygen generated was semi-quantified from the maximum oxygen generation peak height and peak area obtained, which were used as evaluation indices for thermal stability. The semi-quantitative value of the amount of oxygen generated was calculated by injecting pure oxygen gas as a standard sample into the GCMS and extrapolating the calibration curve obtained from the measurement results.
[0168] Example 1 [Crystallization process] A predetermined amount of pure water was placed in a reaction tank (60 L), and the temperature inside the tank was set to 49°C while stirring. At this time, N2 gas was flowed into the reaction tank so that the dissolved oxygen concentration in the reaction tank liquid was 0.8 mg / L. A 2.0 M mixed aqueous solution of nickel sulfate, manganese sulfate, and cobalt sulfate, a 25 mass% sodium hydroxide solution as an alkaline solution, and a 25 mass% ammonia water as a complexing agent were added continuously to the reaction tank simultaneously so that the molar ratio of nickel:manganese:cobalt was 85:10:5 in the reaction tank.
[0169] At this time, the flow rate was controlled so that the residence time of the mixed aqueous solution was 8 hours, and the pH in the reaction tank was adjusted to 12.0 to 12.6 and the ammonia concentration to 10 to 14 g / L. After the reaction tank was stabilized, the slurry containing the nickel manganese cobalt composite hydroxide was collected from the overflow port, and then filtered to obtain a cake of nickel manganese cobalt composite hydroxide (crystallization process). Impurities were washed by passing 1 L of pure water through 140 g of the nickel manganese cobalt composite hydroxide in Denver that was filtered. The powder after filtration was dried to obtain nickel manganese cobalt composite hydroxide particles with a material ratio of nickel, manganese, and cobalt expressed as Ni:Mn:Co=0.85:0.10:0.05.
[0170] [Mixing process] The obtained nickel manganese cobalt composite hydroxide particles, lithium hydroxide, and titanium oxide (TiO2) with an average particle size of 2.5 μm were weighed out so that the mass ratio of lithium:nickel:manganese:cobalt:titanium was 1.05:0.81:0.10:0.05:0.04, and then thoroughly mixed using a shaker mixer (TURBULA Type T2C manufactured by Willy & Bachofen (WAB)) to obtain a lithium mixture.
[0171] [Firing process] The obtained lithium mixture was sintered by holding it in an oxygen stream (oxygen concentration: 90% by volume) at 800° C. for 10 hours, and then crushed to obtain lithium nickel manganese cobalt titanium composite oxide particles.
[0172] [Water washing process] The obtained lithium nickel manganese cobalt titanium composite oxide particles were mixed with 150 parts by mass of water in a ratio of 100 parts by mass, and the mixture was stirred with water for 15 minutes and then subjected to suction filtration using a Nutsche filter to obtain a sediment.
[0173] [Drying process] The obtained sediment was placed in a SUS container, heated to 100° C. using a vacuum dryer for 12 hours, and then heated to 190° C. for 10 hours and left to dry, thereby obtaining a positive electrode active material.
[0174] [evaluation] The (003) crystallite size, amount of eluted lithium, volume average particle size Mv, particle size variation index, and specific surface area of the obtained positive electrode active material are shown in Table 1. As a result of XRD measurement, no heterogeneous phase (impurity phase) other than the hexagonal layer structure was observed. In addition, a coin-type battery CBA shown in FIG. 6 was produced, and the initial charge / discharge capacity and thermal stability were evaluated. The maximum oxygen evolution peak intensity was a relative value to Comparative Example 1 not containing titanium (relative value with Comparative Example 1 set to 100). The manufacturing conditions of the obtained positive electrode active material are shown in Table 1, and the evaluation results are shown in Tables 2 and 3.
[0175] Example 2 A positive electrode active material was obtained and evaluated in the same manner as in Example 1, except that the firing temperature in the firing step was 760° C. The production conditions for the obtained positive electrode active material are shown in Table 1, and the evaluation results are shown in Tables 2 and 3.
[0176] Example 3 In the mixing step, the obtained nickel manganese cobalt composite hydroxide particles, lithium hydroxide, and titanium oxide (TiO2) having an average particle size of 2.5 μm were weighed out so that the mass ratio of lithium:nickel:manganese:cobalt:titanium was 1.05:0.82:0.10:0.05:0.03, and in the firing step, the firing temperature was 780° C., but other than that, a positive electrode active material was obtained and evaluated in the same manner as in Example 1. The manufacturing conditions of the obtained positive electrode active material are shown in Table 1, and the evaluation results are shown in Tables 2 and 3.
[0177] Example 4 A positive electrode active material was obtained and evaluated in the same manner as in Example 3, except that in the baking step, the baking temperature was 790° C. The production conditions of the obtained positive electrode active material are shown in Table 1, and the evaluation results are shown in Tables 2 and 3.
[0178] Example 5 In the mixing step, the obtained nickel manganese cobalt composite hydroxide particles, lithium hydroxide, and titanium oxide (TiO2) having an average particle size of 2.5 μm were weighed out so that the mass ratio of lithium:nickel:manganese:cobalt:titanium was 1.05:0.83:0.10:0.05:0.02, and in the firing step, the firing temperature was 760° C., but other than that, a positive electrode active material was obtained and evaluated in the same manner as in Example 1. Table 1 shows the manufacturing conditions for the obtained positive electrode active material, and Tables 2 and 3 show the evaluation results.
[0179] Comparative Example 1 A positive electrode active material was obtained and evaluated in the same manner as in Example 1, except that in the mixing step, titanium oxide was not prepared, the obtained nickel manganese cobalt composite hydroxide particles were weighed out so that the mass ratio of lithium:nickel:manganese:cobalt was 1.02:0.85:0.10:0.05, the baking temperature in the baking step was 800°C, and the water washing step and the drying step were not performed. The manufacturing conditions of the obtained positive electrode active material are shown in Table 1, and the evaluation results are shown in Tables 2 and 3.
[0180] Comparative Example 2 The lithium nickel manganese cobalt composite oxide particles obtained in the firing step of Comparative Example 1 were subjected to a water washing step and a drying step in the same manner as in Example 1 to obtain and evaluate a positive electrode active material. The manufacturing conditions of the obtained positive electrode active material are shown in Table 1, and the evaluation results are shown in Tables 2 and 3.
[0181] Comparative Example 3 Except for not carrying out the water washing step and the drying step, a positive electrode active material was obtained and evaluated in the same manner as in Example 1. The production conditions of the obtained positive electrode active material are shown in Table 1, and the evaluation results are shown in Tables 2 and 3.
[0182] Comparative Example 4 In the calcination step, the lithium mixture was calcined in an oxygen (oxygen concentration: 60% by volume) stream, and a positive electrode active material was obtained and evaluated in the same manner as in Example 2, except that the water washing step and the drying step were not performed. In addition, as a result of the XRD measurement, a peak attributed to LiTiO2 was confirmed. The manufacturing conditions of the obtained positive electrode active material are shown in Table 1, and the evaluation results are shown in Tables 2 and 3.
[0183] Comparative Example 5 In the mixing step, the nickel manganese cobalt composite hydroxide particles obtained, lithium hydroxide, and titanium oxide (TiO2) having an average particle size of 2.5 μm were weighed so that the ratio of the amounts of lithium:nickel:manganese:cobalt:titanium was 1.01:0.79:0.08:0.05:0.08, and a positive electrode active material was obtained and evaluated in the same manner as in Example 1, except that the water washing step and the drying step were not performed. In addition, as a result of the XRD measurement, a peak attributed to LiTiO2 was confirmed. The manufacturing conditions of the obtained positive electrode active material are shown in Table 1, and the evaluation results are shown in Tables 2 and 3.
[0184] Comparative Example 6 In the crystallization step, a 2.0M mixed aqueous solution of nickel sulfate, manganese sulfate, and cobalt sulfate was added to the reaction tank so that the molar ratio of nickel:manganese:cobalt was 60:20:20, thereby obtaining nickel-manganese-cobalt composite hydroxide particles in which the substance amount ratio of nickel, manganese, and cobalt was expressed as Ni:Mn:Co=0.60:0.20:0.20; in the mixing step, the obtained nickel-manganese-cobalt composite hydroxide particles, lithium hydroxide, and titanium oxide (TiO2) having an average particle size of 2.5 μm were weighed out so that the substance amount ratio of lithium:nickel:manganese:cobalt:titanium was 1.03:0.58:0.20:0.20:0.02; in the firing step, the firing temperature was set to 900° C.; and a water washing step and a drying step were not performed. A positive electrode active material was obtained and evaluated in the same manner as in Example 1, except that The manufacturing conditions for the obtained positive electrode active material are shown in Table 1, and the evaluation results are shown in Tables 2 and 3.
[0185] [Table 1]
[0186] [Table 2]
[0187] [Table 3]
[0188] (Evaluation Results) As shown in Tables 1 to 3, the positive electrode active materials obtained in the examples have extremely good thermal stability and high initial charge / discharge capacity. In all of the positive electrode active materials obtained in the examples, titanium is dissolved in the crystal phase, and no impurity phase (heterogeneous phase) is precipitated.
[0189] On the other hand, the positive electrode active material of Comparative Example 1 has low thermal stability because titanium is not added, and also has a low specific surface area because the washing step and drying step were not carried out.
[0190] In the positive electrode active material of Comparative Example 2, although a water-washing step and a drying step were performed, the initial charge / discharge capacity was slightly decreased, and the maximum oxygen evolution peak intensity and the amount of oxygen evolved were slightly increased, compared with the positive electrode active material of Comparative Example 1, and neither the battery capacity nor the thermal stability was improved.
[0191] The positive electrode active material of Comparative Example 3 was not subjected to a washing step and a drying step, and therefore had a low specific surface area and a low initial discharge capacity. Also, the amount of eluted lithium was large.
[0192] In the positive electrode active material of Comparative Example 4, the oxygen concentration during firing is low, so that part of the titanium cannot be dissolved in the positive electrode active material, and an impurity phase is formed. Therefore, although the thermal stability is good, the initial charge / discharge capacity is significantly reduced due to lithium deficiency and cation mixing in the positive electrode active material. In addition, since the water washing process and the drying process are not performed, the specific surface area is low and the amount of eluted lithium is large.
[0193] In the positive electrode active material of Comparative Example 5, since the amount of titanium added is large, the thermal stability is as good as that of the positive electrode active materials of Examples 1 and 2, for example, but the excessive titanium addition causes a large amount of Ti compounds to precipitate, and the initial charge / discharge capacity is significantly deteriorated. In addition, the increase in the amount of titanium reduces the amount of Ni that contributes to redox, which also affects the capacity decrease, and it is presumed that the thermal stability is apparently improved due to the low electrochemical properties. In addition, since the water washing process and the drying process are not performed, the specific surface area is low and the amount of eluted lithium is large.
[0194] In the positive electrode active material of Comparative Example 6, the nickel ratio of the positive electrode active material is lower than that of the Examples, so that the thermal stability is good, but the initial charge / discharge capacity is significantly deteriorated.
[0195] As described above, the positive electrode active material for lithium ion secondary batteries, the manufacturing method for the positive electrode active material for lithium ion secondary batteries, and the lithium ion secondary battery according to one embodiment of the present invention can provide a positive electrode active material that can provide a lithium ion secondary battery that achieves both high thermal stability and excellent battery characteristics at a high level. Moreover, the present invention can easily produce such a positive electrode active material in industrial-scale production, and it can be said that the industrial value of the present invention is extremely great. [Industrial Applicability]
[0196] In this embodiment, a positive electrode active material for a non-aqueous electrolyte secondary battery that achieves both high thermal stability and excellent battery characteristics at a high level can be obtained by an industrial manufacturing method. This non-aqueous electrolyte secondary battery is suitable as a power source for small portable electronic devices (such as notebook personal computers and mobile phone terminals) that always require high capacity and long life.
[0197] In addition, the secondary battery according to one embodiment of the present invention is superior in safety and capacity and durability in comparison with a battery using a conventional lithium nickel oxide as a positive electrode active material, and therefore can be made smaller and has a longer life, making it suitable as a power source for electric vehicles that are limited in terms of mounting space.
[0198] In addition, the positive electrode active material according to one embodiment of the present invention and the secondary battery using the same can be used not only as a power source for an electric vehicle that is driven purely by electrical energy, but also as a power source for so-called hybrid vehicles that are used in combination with a combustion engine such as a gasoline engine or a diesel engine, or as a stationary storage battery.
[0199] Although the embodiments and examples of the present invention have been described in detail above, those skilled in the art will easily understand that many modifications are possible without substantially departing from the novel features and effects of the present invention. Therefore, all such modifications are intended to be included within the scope of the present invention.
[0200] For example, a term described at least once in the specification or drawings together with a different term having a broader or similar meaning can be replaced with the different term anywhere in the specification or drawings. The configurations and operations of the positive electrode active material for lithium ion secondary batteries, the lithium ion secondary battery, and the method for producing the positive electrode active material for lithium ion secondary batteries are not limited to those described in the respective embodiments and examples of the present invention, and various modifications are possible. [Explanation of symbols]
[0201] CBA…Coin cell battery PE: Positive electrode (electrode for evaluation) NE: negative electrode (lithium metal) SE…Separator GA…Gasket WW…Wave washer PC…Positive electrode can NC: Negative electrode can
Claims
1. A positive electrode active material for a lithium ion secondary battery, comprising a lithium nickel manganese composite oxide composed of secondary particles formed by agglomeration of a plurality of primary particles, The lithium nickel manganese composite oxide has a hexagonal layered structure and contains lithium (Li), nickel (Ni), manganese (Mn), titanium (Ti), and optionally, an element M (M) which is at least one element selected from Co, V, Mg, Mo, Ca, Cr, Ta, Na, W, Fe, Zn, B, Si, P, Zr, Nb, and Al; The ratio of the amounts of substances of the elements is expressed as Li:Ni:Mn:M:Ti=a:(1-x-y-z):x:y:z (where 0.97≦a≦1.25, 0.03≦x≦0.15, 0≦y≦0.15, and 0.01≦z≦0.05), In an XRD measurement of the positive electrode active material, the ratio of the total amount of peak intensities of the strongest lines of the titanium compound to the (003) diffraction peak intensity, which is the strongest line of the hexagonal layered structure, is 0.2 or less; The (003) crystallite size measured by XRD is 80 nm or more and less than 160 nm; The specific surface area measured by the BET method is 0.7 m 2 / g or more 4.0m 2 / g or less, Positive electrode active material for lithium-ion secondary batteries.
2. 2. The positive electrode active material for lithium ion secondary batteries according to claim 1, wherein [(D90-D10) / Mv], which indicates a particle size variation index calculated from volume-based D90 and D10 in a particle size distribution measured by a laser diffraction scattering method and the volume average particle size (Mv), is 0.80 or more and 1.20 or less.
3. 3. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein the volume average particle diameter Mv is 8 μm or more and 20 μm or less.
4. The positive electrode active material for lithium ion secondary batteries according to any one of claims 1 to 3, wherein the amount of lithium eluted into water when immersed in water is 0.2 mass% or less based on the entire positive electrode active material.
5. A positive electrode active material for a lithium ion secondary battery described in any one of claims 1 to 4, wherein in an XRD measurement of the positive electrode active material, the ratio of the total amount of peak intensity of the strongest line of the titanium compound to the (003) diffraction peak intensity, which is the strongest line of the hexagonal layered structure, is 0.
6. A method for producing a positive electrode active material for a lithium ion secondary battery, comprising: A mixing step of mixing at least a nickel-manganese composite compound, a titanium compound, and a lithium compound to obtain a mixture; a calcination step of calcining the mixture in an oxidizing atmosphere having an oxygen concentration of 80% by volume or more and 100% by volume or less at 700° C. or more and 950° C. or less to obtain the lithium nickel manganese composite oxide; a water washing step of mixing 100 parts by mass of the lithium nickel manganese composite oxide with water in a ratio of 50 parts by mass to 200 parts by mass, stirring the mixture, and then subjecting the mixture to solid-liquid separation; a drying step of drying the lithium nickel manganese composite oxide after washing with water; Equipped with The nickel manganese composite compound contains nickel (Ni), manganese (Mn), and optionally, an element M (M) which is at least one element selected from Co, V, Mg, Mo, Ca, Cr, Ta, Na, W, Fe, Zn, B, Si, P, Zr, Nb, and Al, and the ratio of the amounts of substances of the elements is Ni:Mn:M=(1-x-y):x:y (where 0.03≦x≦0.15, 0≦y≦0.15); The titanium compound has a volume average particle size Mv of 0.01 μm or more and 5 μm or less, The mixture has a ratio (Li / Me) of the amount of substance of lithium (Li) to the total amount of substance (Me) of nickel, manganese, the element M, and titanium contained therein, of 0.97 or more and 1.25 or less, and a ratio (Ti / Me) of the amount of substance of titanium (Ti) to the total amount of substance (Me) of nickel, manganese, the element M, and titanium contained therein, of 0.01 or more and 0.05 or less, In an XRD measurement of the positive electrode active material, the ratio of the total amount of the diffraction peak intensity of the strongest line of the titanium compound to the (003) diffraction peak intensity which is the strongest line of the hexagonal layered structure is 0.2 or less; The (003) crystallite size measured by XRD is 80 nm or more and less than 160 nm; A method for producing a positive electrode active material for a lithium ion secondary battery.
7. 7. The method for producing a positive electrode active material for a lithium ion secondary battery according to claim 6, wherein the titanium compound has a volume average particle size Mv of 0.05 μm or more and 3 μm or less.
8. The method for producing a positive electrode active material for a lithium ion secondary battery according to claim 6 or 7, wherein the titanium compound is titanium oxide.
9. A method for producing a positive electrode active material for a lithium ion secondary battery described in any one of claims 6 to 8, wherein in an XRD measurement of the positive electrode active material, the ratio of the total amount of the diffraction peak intensity of the strongest line of the titanium compound to the (003) diffraction peak intensity, which is the strongest line of the hexagonal layered structure, is 0.
10. A lithium ion secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, the positive electrode including the positive electrode active material according to any one of claims 1 to 5.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary battery
JP1992319260A
Positive electrode active material for nonaqueous system secondary battery and its manufacturing method, and nonaqueous system secondary battery using the same
JP2002151071A
Cathode active substance for nonaqueous electrolyte secondary battery, cathode mixture for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2005251716A
Lithium transition metal based compound powder, its manufacturing method, and positive electrode material for lithium secondary battery and lithium secondary battery using it
JP2011108554A
Positive electrode composition for nonaqueous electrolyte secondary battery
JP2013239434A